Hierarchically Porous SnO2 Coupled Organic Carbon for CO2 Electroreduction. Issue 22 (15th October 2020) - Kuang, Zhaoyu; Zhao, Wanpeng; Peng, Chunlei; Zhang, Qingming; Xue, Yi; Li, Zhaoxia; Yao, Heliang; Zhou, Xiaoxia; Chen, Hangrong
Abstract: Converting CO2 into value‐added chemicals or fuels by electrochemical CO2 reduction reaction (CO2 RR) has aroused great interest, whereas designing highly active and selective electrocatalysts is still a challenge. Herein, a novel kind of electrochemical catalyst composed with SnO2 and organic carbon (OC), named as SnO2 /OC, was facilely constructed for CO2 RR. The obtained SnO2 /OC exhibits both high faradaic efficiency for formate (∼75 %) and carbon products (∼95 %) as well as excellent stability. High surface area with hierarchically porous structure and the homogeneous formation of Sn−O−C linkages in SnO2 /OC jointly promote the adsorption and activation of CO2, as well as fast transport of reactants and products. Abstract : Adjusted, enlarged, tuned : A hierarchically porous electrocatalyst SnO2 coupled with organic carbon (OC) is described. The partially retained OC has not only adjusted pore structure and enlarged surface area, but also tuned electronic structure of Sn to form homogeneous Sn−O−C linkages, which jointly enhances the CO2 electroreduction performance.